2011
DOI: 10.2298/hel1154059p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SSR markers for hybridity and seed genetic purity testing in sunflower (Helianthus annuus L.)

Abstract: The genuineness of a hybrid is one of the most important characteristics of good quality seed. In order to identify pure hybrid and pollen shedders/ offtypes an investigation was performed to identify an ideal SSR marker. 58 primer pairs were screened to identify the specific marker associated with each hybrid and parental lines. Hybrid KBSH-44 could be clearly identified by using ORS 309 and ORS 170, based on the banding pattern resolved on polyacrylamide gel (6%). The complementary banding pattern of both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Recently attempts to grow sunflower kernels for preparing products are being made (Shadakshari, Y. G. Geneticist, AICRP Sunflower, GKVK, UAS, Bengaluru, Personnel communication 2010). Several cultivars such as KBSH 1, KBSH 41, KBSH 42, KBSH 44, KBSH 53, Surajmukhi etc., (Pallavi et al 2011) are available. Screening some of varieties showed that KBSH 44 was having a good hullability (Muttagi, GKVK, UAS, Bengalu, unpublished work, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently attempts to grow sunflower kernels for preparing products are being made (Shadakshari, Y. G. Geneticist, AICRP Sunflower, GKVK, UAS, Bengaluru, Personnel communication 2010). Several cultivars such as KBSH 1, KBSH 41, KBSH 42, KBSH 44, KBSH 53, Surajmukhi etc., (Pallavi et al 2011) are available. Screening some of varieties showed that KBSH 44 was having a good hullability (Muttagi, GKVK, UAS, Bengalu, unpublished work, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The SSR markers identified had both female and male specific bands and are useful in genetic purity testing. The use of SSR markers for genetic purity testing has already been demonstrated in maize (Daniel et al, 2012;Mrutu, 2015;Simon and Lovasz, 2016;Wu et al, 2010); rice (Bora et al, 2016;Galal et al, 2014;Moorthy et al, 2011;Sudharani et al, 2013), pearl millet (Nagawade et al, 2016), eggplant (Reddy et al, 2015), soybean (Zhang et al, 2014), cauliflower (Zhao et al, 2012) and in sunflower (Pallavi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Among available DNA markers systems, PCR based co-dominant SSRs (also known commonly as microsatellites) are preferred for genotyping because of their reproducibility, abundance and amenability to high throughput screening. The SSR markers are of great importance for rapid assessment of hybrid and parental line seed purity (Dongre et al, 2011(Dongre et al, , 2012Pallavi et al, 2011;Reddy et al, 2011Reddy et al, , 2015. These markers allow the early identification of true interspecific hybrids for further evaluation and crossing, and simultaneously, enable the early disposal of non-hybrids, thus delivering substantial savings in time and resources.…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%
“…These results are in close agreement with Yoshitola (2002). Since STMS and STS markers cover whole genome, they show polymorphism in DNA banding pattern of different genotypes which reveal the variation and allelism (marker alleles) in larger quantity (Yashitola , 2002;Nandkumar , 2004;Sayyed , 2009;Antonova , 2006;Sundaram , 2008 ;Jaikishan , 2010;Pallavi , 2011Kumar , 2012Vikas 2014;Kumar 2016).…”
Section: Resultsmentioning
confidence: 99%